Penyuluhan Pendidikan Karakter Era Globalisasi Pada Masyarakat Desa A Widodo Kecamatan Tugumulyo Kabupaten Musi Rawas - Agus Susilo; Sarkowi Sarkowi; Mita Anggelia (CERED Indonesia Publishing, 2021)
The purpose of this research is related to the needs of the people of A Widodo Village for character education, so that the theme of character education education in the era of globalization is taken in the community of A Widodo Village, Tugumulyo District, Musi Rawas Regency. The scope of this community service program is that the young generation in A Widodo Village is currently very vulnerable to the rampant flow of globalization, so community service activities can be a solution to the problem. The method of implementation in this community service activity is carried out with the presentation of material by each of the speakers followed by a question and answer discussion to discuss current character education. in the discussion the question and answer became a reference for the solution to the problem of character education for young people today. Analytical techniques and results of activities, namely activities carried out to support the tri darma of higher education resulted in several solutions that could be developed by the people of A Widodo Village in implementing character education for their children. The people of A Widodo Village were very enthusiastic in participating in this activity. some people ask that community service activities like this can be resumed. The community also hopes that the Lecturers of STKIP PGRI Lubuklinggau can become partners of Desa A Widodo in various activities related to education.